Analisa Pengaruh Cleaning Kondensor Terhadap Vibrasi CWP 2C Vakum Kondensor Dan Temperatur Cooling PLTU Paiton 2 - Vendy Antono; Dika Wahyu Wijaya (JURNAL POWERPLANT, 2014)
In the process of production of the power plant cooling water system has a very important role to change the vapor phase from the expansion turbine into water stored in Hotwell. The condenser is equipment which becomes the venue for the process, but keep in mind the level of cleanliness of the condenser becomes an important factor because it can reduce the heat transfer in the condenser and reduces the cooling process. Moreover, it can also result in other equipment eg in CWP (circulating water pump) increased vibration due to flow of pumped water can not flow the maximum because of blockage in the tube-tube condenser can for garbage, excrement of marine life, or the rubber peeled off later cover tube-tube condenser. This will also result in the efficiency of the unit as well as derating occurs during the process of cleaning the condenser. Cleaning the condenser lowers vibration values ​​CWP 2C Motor inboard side Axial from 6754 mm / s to 1080 mm / s and horizontal outboard motor side of 4645 mm / s to 2827 mm / s according to ISO 10816-3 standard vibration value falls within the normal conditions of operation .Kenaikan dry vacuum condenser before becoming 695 mmHg 683 mmHg after cleaning the condenser this is because the maximum heat transfer process. Mass amounts of water cooling which increased from 15133.88 kg / s into 19221.1 kg / s cause the temperature difference cooling water in and out decreased from before cleaning the condenser is 13 0C becomes 8.6 0C.